The Use of Social and Affective Strategies to Improve the 7th Graders’ Speaking Participation and Performance - Carinta Rizki Yuniar; Utari Praba Astuti; Furaidah Furaidah (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: The objective of this study is to improve the students’ speaking participation and performance with the use of social and affective strategies. The research design used in the study was Classroom Action Research (CAR). The stage of CAR was adapted from Kemmis and McTaggart (1988) which consists of planning, implementing, observing, and reflecting. The subjects of the research were 30 seventh graders of class VII-H at SMPN 9 Malang in the second semester of academic year 2019/2020. This study was conducted directly at SMPN 9 Malang in one cycle of CAR in three meetings. To collect the data, an interview guide, an observation checklist, a field note and a speaking rubric were used as instruments. The findings of study showed that the students’ speaking participation and performance successfully improved after implementing social and affective strategies. The criterion of success set by the researcher was 70. The mean speaking score for the preliminary test and the final test increased from 60.4 to 77.2. The use of social and affective strategies improved students’ interaction with other students as well as managed their attitude, emotion, and motivation in speaking. Keywords: speaking skill, social strategy, affective strategy Abstrak: Penelitian ini bertujuan untuk meningkatkan partisipasi dan performa berbicara siswa dalam Bahasa Inggris dengan penggunaan Strategi Sosial dan Afektif. Desain penelitian yang digunakan dalam penelitian ini adalah Penelitian Tindakan Kelas (PTK). Tahapan PTK yang digunakan diadaptasi dari Kemmis dan McTaggart (1988) yang terdiri dari perencanaan, pelaksanaan, pengamatan, dan refleksi. Terdapat sejumlah 30 siswa yang berasal dari kelas VII-H SMPN 9 Malang semester genap tahun ajaran 2019/2020 yang terlibat sebagai subjek penelitian. Penelitian ini dilaksanakan langsung di SMPN 9 Malang dalam satu siklus PTK yang terdiri dari tiga pertemuan. Untuk mengumpulkan data, peneliti menggunakan pedoman wawancara, checklist observasi, catatan lapangan dan rubrik berbicara sebagai instrumen. Temuan penelitian menunjukkan bahwa partisipasi dan performa berbicara siswa berhasil ditingkatkan setelah menerapkan Strategi Sosial dan Afektif. Kriteria keberhasilan yang ditetapkan peneliti adalah 70. Nilai rata-rata berbicara siswa sebelum kedua strategi diterapkan dan setelah diterapkan terbukti meningkat dari 60,4 menjadi 77,2. Penggunaan Strategi Sosial dan Afektif meningkatkan interaksi siswa dengan siswa lain serta mengatur sikap, emosi, dan motivasi mereka dalam berbicara. Kata kunci: keterampilan berbicara, strategi social, strategi afektif